2001
DOI: 10.1038/sj.bjp.0704081
|View full text |Cite
|
Sign up to set email alerts
|

Differential prevention of morphine amnesia by antisense oligodeoxynucleotides directed against various Gi‐protein α subunits

Abstract: 1 The e ect of the i.c.v. administration of pertussis toxin (PTX) and antisense oligodeoxynucleotide directed against the a subunit of di erent Gi-proteins (anti-Gia 1 , anti-Gia 2 , anti-Gia 3 ) on amnesia induced by morphine was evaluated in the mouse passive avoidance test. 2 The administration of morphine (6 ± 10 mg kg 71 i.p.) immediately after the training session produced amnesia that was prevented by PTX (0.25 mg per mouse i.c.v.) administered 7 days before the passive avoidance test. 3 Anti-Gia 1 (6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The activation of these receptors, which inhibit adenylyl cyclase through Gi/o types of G-proteins (Law et al, 1999(Law et al, , 2000, is required for morphine to induce amnesia in the mouse passive avoidance test (Galeotti et al, 2001). Interestingly, the present results showed that intra-CA1 administration of different doses of lithium on the test day also reversed the decrease in the step-down latency induced by posttraining morphine.…”
Section: Discussionmentioning
confidence: 56%
“…The activation of these receptors, which inhibit adenylyl cyclase through Gi/o types of G-proteins (Law et al, 1999(Law et al, , 2000, is required for morphine to induce amnesia in the mouse passive avoidance test (Galeotti et al, 2001). Interestingly, the present results showed that intra-CA1 administration of different doses of lithium on the test day also reversed the decrease in the step-down latency induced by posttraining morphine.…”
Section: Discussionmentioning
confidence: 56%
“…Numerous experiments demonstrated negative effects of morphine, enkephalins, and their derivatives on active and passive avoidance conditioning (Martinez, 1992;Galeotti et al, 2001). Similar data were obtained during learning with oxidative reinforcement-both during the development of operative responses and in maze tests (Vlasova et al, 1983;Pakarinen et al, 1995).…”
Section: Discussionmentioning
confidence: 90%